Pengaruh Metode Glenn Doman terhadap Kemampuan Interaksi Sosial Anak Autis di SLB-B dan Autis TPA (Taman Pendidikan dan Asuhan) Kabupaten Jember (The Effect of Glenn Doman Method towards Autistic Social Interaction Ability in SLB-B and Autistic TPA (Tama - Ragil Deshinta; Ratna Sari Hardiani; Erti Ikhtiarini Dewi (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Autism is a complex developmental disability that typically appears during the first three years of life, characterized by disturbance of social interaction, behavior, and communication skills. Disturbance of social interaction cause on autism difficulties to get work, activities, and can not fulfill basic human need. The objective of this research was analyze the effect of glenn doman method towards autistic child’s social interaction ability. This research used pre experimental with one group pretest posttest design approach. The sample was 17 autistic using of total sampling. Data was analyzed with wilcoxon match pair test. The result showed that P value was 0,001 (0,001 < α=0,05), it means that there was an effect of glenn doman method toward autistic child’s social interaction ability in SLB-B and Autistic TPA, Jember Regency. Based on the result, it is suggested for the family with an autistic child to give glenn doman method to exercise the autistic child’s social interaction ability. Keywords: Glenn Doman Method, Social Interaction Ability, Autistic